Bioinformatic identification of connective tissue growth factor as an osteogenic protein within skeletal muscle. Issue 12 (December 2014) - Forrester, Steven J.; Kawata, Keisuke; Lee, Hojun; Kim, Ji‐Seok; Sebzda, Kelly; Butler, Tiffiny; Yingling, Vanessa R.; Park, Joon‐Young
Abstract Aging is associated with increasing incidence of osteoporosis; a skeletal disorder characterized by compromised bone strength that may predispose patients to an increased risk of fracture. It is imperative to identify novel ways in which to attenuate such declines in the functional properties of bone. The purpose of this study was to identify, through in silico, in vitro, and in vivo approaches, a protein secreted from skeletal muscle that is putatively involved in bone formation. We performed a functional annotation bioinformatic analysis of human skeletal muscle‐derived secretomes (n = 319) using DAVID software. Cross‐referencing was conducted using OMIM, Unigene, UniProt, GEO, and CGAP databases. Signal peptides and transmembrane residues were analyzed using SignalP and TMHMM software. To further investigate functionality of the identified protein, L6 and C2C12 myotubes were grown for in vitro analysis. C2C12 myotubes were subjected to 16 h of glucose deprivation (GD) prior to analysis. In vivo experiments included analysis of 6‐week calorie restricted (CR) rat muscle samples. Bioinformatic analysis yielded 15 genes of interest. GEO dataset analysis identified BMP5, COL1A2, CTGF, MGP, MMP2, and SPARC as potential targets for further processing. Following TMHMM and SignalP processing, CTGF was chosen as a candidate gene. CTGF expression level was increased during L6 myoblast differentiation (P < 0.01). C2C12 myotubes showed no change in response to GD. Rat soleus muscle samples exhibited an increase in CTGF expression (n = 16) in response to CR (35%) (P < 0.05). CTGF was identified as a skeletal muscle expressed protein through bioinformatic analysis of skeletal muscle‐derived secretomes and in vitro/in vivo analysis. Future study is needed to determine the role of muscle‐derived CTGF in bone formation and remodeling processes.